Not to be judged by its cover - Terre Blanche, Martin; Mbatha, Khonzi (PINS-Psychology in Society, 2024)
Mountian, Ilana (2013) Cultural ecstasies: Drugs, gender and the social imaginary. London: Routledge. ISBN 978-0-415-58386-2 pbk. Pages viii + 160 The first thing to know about this book is that it is rather nicely, but somewhat misleadingly, packaged. The back cover starts with an endorsement by Nancy Campbell in which she claims that the book “weaves together an intricate web for the purpose of giving voices to those who are defined and silenced by virtue of their addictions”. If you take this to mean, as we did, that the book reports on and valorises ways that drug users themselves (as opposed to experts and such) speak about doing drugs, then know that this is not the case. Instead, it unpacks and critiques mainstream writing and talk about drugs – of the sort that circulates in churches, newspapers, schools and the criminal justice system – in the process perhaps, to some extent, forging a new language that drug users (and others) could tap into.